Computational Flow Modeling for Chemical Reactor Engineering. - Ranade, Vivek V. (Elsevier, 2001)
This book describes how modeling fluid flow in chemical reactors may offer solutions that improve design, operation, and performance of reactors. Chemical reactors are any vessels, tubes, pipes, or tanks in which chemical reactions take place. Computational Flow Modeling for Chemical Reactor Engineering will show the reactor engineer how to define the specific roles of computational flow modeling, select appropriate tools, and apply these tools to link reactor hardware to reactor performance. Overall methodology is illustrated with numerous case studies. Industry has invested substantial funds.
Keywords: Chemical reactors -- Fluid dynamics -- Mathematical models.; elektronické knihy; electronic books